2022
DOI: 10.3390/math10060901
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Fractions of Learners in Slovakia

Abstract: In this research, we set two main goals: to provide empirical data that point to the knowledge of fractions among fifth-grade primary school pupils on a national scale; and to determine the level of knowledge about fractions among university students, including future primary school teachers. We used two tests—the national-wide test T5 for the fifth-graders (a research sample of approximately 45,000 pupils), and the modified fraction test based on Sfard’s theory of reification, for the university students (162… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Our previous studies have shown that math anxiety interferes with cognitive processing. With math anxiety, there is a decrease in working memory capacity, which is also related to students' results in mathematics [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that math anxiety interferes with cognitive processing. With math anxiety, there is a decrease in working memory capacity, which is also related to students' results in mathematics [24], [25].…”
Section: Discussionmentioning
confidence: 99%